Development metrics measurement level for component reusability evaluation approach (CREA) - Suryani Ismail; Fatihah Mohd; Masita Abdul Jalil; Wan M.N. Wan Kadir (Institute of Advanced Engineering and Science, 2019)
The study of software component reuse is rising in software development field and one of the methods used to reduce the production cost and time. Among the problems faced by software developers in component reuse, is the difficulty to determine which set of components are suitable to use in new software development. Thus, this study was conducted with the purpose; to define the characteristics of software component reusability evaluation approach (CREA) based on experienced software developer’s feedback, and to estimate the measurement level for each of the predefined metric. Three characteristics and sub characteristics, namely understandability (documentation level and observality), adaptability (customizability), and portability (external dependency) were identified that have been used to develop the metrics for CREA. The result for all metrics will be used as an input to the fuzzy inference system (FIS) for measuring the reusability level of the component.